Sustainability of Agriculture in Miami-Dade County: Considering Water Supply - Kati W. Migliaccio (EDIS, 2007)
AE429, a 7-page illustrated fact sheet by Kati W. Migliaccio, discusses water availability, factors that influence water availability, agricultural water use, and irrigation efficiency as they relate to Miami-Dade County. Includes references. Published by the UF Department of Agricultural and Biological Engineering, August 2007.